Marketing for special and academic libraries : a planning and best practices sourcebook - Higginbottom, Patricia C.; Gordon, Valerie S. (Medical Library Association books., 2016)
Marketing for Special and Academic Libraries is an easy-to-follow, practical, easily-implementable, 21st-Century marketing book for academic and special libraries. Written by two practicing librarians who are passionate about communicating with user, the book provides both the inspiration and drive to market your library and practical tips and suggestions on how to do that effectively.